A thoracic venous aneurysm mimicking a chronic expanding haematoma. (23rd November 2018) - Tsujimura, Ryusuke; Kojima, Toshio; Osaka, Eiji; Hao, Hiroyuki
Abstract: Thoracic venous aneurysms are rare, and bleeding is possible. A 9-year-old female patient presented with a thoracic wall mass. No blood flow was observed in the mass, and a chronic expanding haematoma was suspected based on the differential diagnosis. However, the venous structure was identified in the wall of the mass on pathological examination, and the diagnosis of the venous aneurysm was thereby established. Because the venous aneurysm contains fresh blood and bleeding can be profuse when such lesions are not properly handled during a surgical procedure, making the visibility of the surgeon poor, the venous aneurysm must be included in the differential diagnosis.